Perceived Constraints and Suggestions revealed by SDAH Personnel for Im proving the Livestock Extension Service Delivery to Women Farmers (Indian Journal of Animal Production and Management, 2025)
Present study was conducted to identify various constraints perceived by  SDAH Personnel in delivering the livestock extension services in central  plain zone of Uttar Pradesh. An ex-post facto and exploratory research  design were used to study the perceived constraints in four districts of Uttar  Pradesh. A total 16 indicators of constraints were selected through previous  studies and experts opinion. Data were collected by personal interview  from 120 (60 Veterinary Officer and 60 Livestock Extension Officers) State  Department of Animal Husbandry personnel randomly selected from  available list at the district head quarter. The study revealed that, livestock  extension activities suffer due to inadequate veterinary staff and this is  the most severe constraint followed by inadequate budget allotment and  over burdening of other paper work with respective ranks I, II and III.  Recruitment of more number women SDAH personnel, organizing women  targeted livestock extension activities, establishing separate grassroot level  livestock extension wing were the major common suggestion revealed by the  Veterinary Officers and the Livestock Extension Officers.
Keywords: Constraints, Livestock Extension Services, Livestock Extension Officers, State Department of Animal Husbandry (SDAH) and Veterinary Officers.